Assessment of lead food contamination and dietary intake in a Northern Italian population. (30th September 2020) - Malavolti, M; Filippini, T; Fairweather-Tait, S J; Malagoli, C; Vescovi, L; Vinceti, M
Abstract: Background: Lead is a heavy metal naturally occurring in the environment and also released by some anthropogenic activities. Food is one the major sources of human exposure for non-occupationally exposed individuals. In this study, we aimed at characterizing lead (Pb) content in foods consumed in Northern Italy population, in order to estimate its dietary intake. Methods: We measured lead content in 908 food and beverage samples bought at small shops and supermarkets of the Northern Italy provinces of Modena and Reggio Emilia, through inductively coupled plasma mass spectrometry. We used a validated semi-quantitative food frequency questionnaire to assess the dietary habits of a representative sample of 719 individuals (319 males and 400 females) aged 18-87 years residing in Northern Italy (Emilia Romagna). We estimated weekly dietary intakes of Pb, and we compared them with safety standards set by the European Food Safety Authority (EFSA). Results: In this population, vegetables and vegetables products were the main contributors to Pb intake. The highest levels of Pb were in edible offal, and then in crustaceans, dry fruits, chocolate free sweet confectionery, and coffee and tea as beverages. In general, Pb levels in our samples were comparable and did not exceed the average contamination levels reported by EFSA in various European countries. We found a comparable average Pb intake in both sexes. Average weekly intake of Pb was below EFSA recommended provisional tolerable weekly intake. Conclusions: Our study provides an updated assessment of lead exposure through diet in a Northern Italian community. Although environmental lead contamination and exposure have markedly decreased in the last decades, recent evidence pointed out that a safety threshold value cannot yet be established for prevention of adverse effects due to lead exposure, since even low levels of lead intake may still increase the risk of chronic renal disease and hypertension. Key messages: Food is one the major lead sources of human exposure for non-occupationally exposed individuals. Lead levels in Northern Italian population studied are comparable and do not exceed the average contamination levels reported by European Food Safety Authority in various European countries.